Analysis Of Bus-Based Tracking GPS (Global Positioning System) - Tama R A; Thamrin T (International Conference on Engineering and Technology Development (ICETD), 2017)
The development of the era and the technology is now quite a lot of us feel the benefits in many ways, more and more companies that created everything that always related to technology, and after the authors observe the company is taking a crack of the individual nature of today who like to be something that is simple, practical, and easy to use. Lots of companies are trying to exploit the situation, but here I will see in terms of transportation, we can see that there are some companies that take a crack at creating a variety of applications that lead to transport, to make it easier for people who want to travel without having to wait a long time , can be timely, can come directly to localized, such as an application example Gojek, Uber, and Grabtaxi